Characteristics and Applications of Nanoparticles in Manipulation of Livestock Reproductive Hormones - Fitra Aji Pamungkas; Elizabeth Wina (Indonesian Center for Animal Research and Development, 2015)
The research on hormone packaged in very small size particles began to develop in recent years. Nanoparticles are defined as particulate dispersions or solid particles with a polymer used as a component of potential hormone carrier as effective drug because of their ability to circulate and to release in a controlled period in the body. This review describes a variety of methods, characteristics and applications of nanoparticles hormones usages for animals. In general, several studies indicated that the formation of the hormone nanoparticles using polymer accompanied by distributing a good and stable of molecular mass, can be used as a carrier component of hormones as well as considering the negative effect.